The efficacy of intranasal leptin for opioid-induced respiratory depression depends on sex and obesity state - Singer, Michele L.; Shin, Mi-Kyung; Kim, Lenise J.; Freire, Carla; Aung, O; Pho, Huy; East, Joshua A.; Sgambati, Frank P.; Latremoliere, Alban; Pham, Luu V.; Polotsky, Vsevolod Y. (Frontiers in Physiology, 2023)
Opioid-induced respiratory depression (OIRD) is the primary cause of death associated with opioids and individuals with obesity are particularly susceptible due to comorbid obstructive sleep apnea (OSA). Repeated exposure to opioids, as in the case of pain management, results in diminished therapeutic effect and/or the need for higher doses to maintain the same effect. With limited means to address the negative impact of repeated exposure it is critical to develop drugs that prevent deaths induced by opioids without reducing beneficial analgesia. We have previously shown that intranasal (IN) leptin can reverse apneas, hypoventilation, and upper airway obstruction while enhancing analgesia following acute morphine administration in obese males. Here we hypothesize that OIRD as a result of chronic opioid use can be attenuated by administration of IN leptin while also maintaining analgesia in both lean mice and mice with diet-induced obesity (DIO) of both sexes. To test this hypothesis, an opioid tolerance protocol was developed and a model of OIRD in mice chronically receiving morphine and tolerant to morphine analgesia was established. Subsequently,